Method for preparing photocatalytic membrane with hydrophilic and light trapping dual-function microstructure by using pulse laser

The preparation of a photocatalytic film with a dual-function microstructure of hydrophilic and trapped light through pulsed laser solves the problems of difficulty in recycling photocatalytic powder and the reduction of catalytic activity, and achieves efficient photocatalytic degradation performance and recyclability, which is suitable for large-scale applications.

CN119114165APending Publication Date: 2024-12-13ZHEJIANG MOKE LASER INTELLIGENT EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411382262.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing photocatalytic powder recovery is difficult, the catalytic activity of the photocatalytic film is reduced, and the performance is slowed down during the sewage degradation process, which limits the promotion and industrial application of photocatalytic degradation technology.

Method used

Pulse laser is used to prepare a photocatalytic film with a dual-functional microstructure of hydrophilic and trapped light. PVDF powder is dissolved by N,N-dimethylformamide and acetone solvent, and calcium titanate and graphite oxide prepared by laser liquid ablation are added. The olefin composite material forms patterned microstructures to improve the reusability and anti-reflection properties of the photocatalyst.

Benefits of technology

It achieves higher photocatalytic activity and recyclability, maintains long-term and stable photocatalytic degradation performance, improves pollutant removal efficiency and incident light utilization rate, and is suitable for large-scale preparation and industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114165A_ABST
    Figure CN119114165A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a photocatalytic membrane with a hydrophilic and light trapping dual-function microstructure by using pulse laser, which comprises the following steps: firstly, blending a calcium titanate and graphene oxide composite material (CTO / rGO composite material) prepared by laser liquid phase ablation with polyvinylidene fluoride (PVDF) by using a blending method to prepare a CTO / rGO photocatalytic membrane; and then the surface of the CTO / rGO photocatalytic membrane is etched by pulse laser to obtain a pattern microstructure surface with double functions of hydrophilicity and reflection resistance, so that the reusability of the photocatalyst is improved, the photocatalytic degradation effect is enhanced, and the long-term stable photocatalytic degradation capability of the photocatalyst is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a method for preparing a photocatalytic film with a hydrophilic / light-trapping dual-functional microstructure by using pulsed laser. Background Art

[0002] The rapid development of industry has brought great convenience to our lives, but it has also inevitably produced a large amount of toxic and harmful industrial wastewater, which has not only caused damage to the ecological environment, but also directly or indirectly threatened human health. Although the existing sewage treatment technology has achieved initial results, it is accompanied by a large amount of energy consumption. Therefore, it is imperative to develop a new technology that can achieve wastewater degradation through clean and renewable energy.

[0003] Since Fujishima reported in 1972 that titanium dioxide (TiO2) decomposes water to produce hydrogen under light, the world has conducted a lot of research on semiconductor photocatalytic technology and successfully applied this technology to the field of wastewater degradation. However, the existing semiconductor materials have low light utilization, large bandgap, easy carrier recombination and other problems, resulting in unsatisfactory wastewater degradation effects, which limits the large-scale promotion of photocatalytic wastewater degradation technology. In recent years, people have developed a variety of modification methods to improve the photocatalytic performance of semiconductors to achieve efficient wastewater degradation, such as precious metal deposition, element doping and semiconductor composites, and it has been proven that chemical methods such as hydrothermal method, sol-gel method, one-step combustion method, etc. can effectively achieve semiconductor modification.

[0004] Although semiconductor modification can improve photocatalytic activity, the modified photocatalyst still exists in the form of powder, so there are problems of difficult recovery and low recycling rate in actual industrial applications. Based on this, researchers have tried to load powdered photocatalysts onto polymer polymers, which not only improves the recovery rate of powdered photocatalysts, but also reduces the recycling cost. At present, the main methods for combining photocatalysts with polymer membranes are surface coating, surface chemical method and blending method. However, fixing the photocatalyst on the polymer membrane will inevitably lead to a decrease in photocatalytic activity. At the same time, as the photocatalytic degradation proceeds, the photocatalytic performance will also be greatly slowed down. Therefore, how to effectively improve the photocatalytic activity of the photocatalytic membrane and the long-term stability of the photocatalytic performance is an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a photocatalytic film with a hydrophilic and light-trapping dual-functional microstructure using pulsed laser, which solves the problems of difficulty in recycling existing photocatalytic powders and reduced catalytic activity of photocatalytic films. The prepared photocatalytic film has higher light-trapping ability and hydrophilicity, thereby obtaining higher photocatalytic activity and good recyclability, and has long-term stable photocatalytic degradation performance. The preparation method is simple in process and highly repeatable, and is conducive to large-scale preparation, promotion and industrial application.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure by using a pulsed laser, which comprises the following steps:

[0008] (1) Using N,N-dimethylformamide (DMF) and acetone as solvents, adding PVDF (polyvinylidene fluoride) powder thereto, and stirring until PVDF is completely dissolved;

[0009] (2) adding calcium titanate and graphene oxide composite material (CTO / rGO composite material) prepared by laser liquid phase ablation to the PVDF solution dissolved in step (1), and continuing to stir to obtain a uniformly dispersed mixed solution;

[0010] (3) placing the mixed solution obtained in step (2) in a vacuum desiccator and maintaining the pressure for 3 to 5 hours to remove bubbles in the mixed solution;

[0011] (4) drying the mixed solution after treatment in step (3) in a water bath at 70 to 90° C. for 6 to 8 hours to obtain a photocatalytic film;

[0012] (5) The photocatalytic film prepared in step (4) is subjected to a picosecond laser precision processing system to form a patterned microstructure on its surface; specifically, the laser irradiation parameters are set: the laser wavelength, scanning speed, laser energy, spot size, spot overlap rate, and scanning area position and size are fixed, firstly a square with a side length of 2 to 10 mm is drawn, and a cross groove with a spacing of dx is filled in the square, and the dx range is 120 to 180 μm. After the laser scans the square 50 to 100 times, the next square is scanned to obtain the desired patterned microstructure; wherein, the laser scans once in the x-axis direction and once in the y-axis direction, which is recorded as one laser scan.

[0013] Furthermore, in the step (1), the volume ratio of N,N-dimethylformamide to acetone in the solvent is 7:3, and the ratio of the mass of PVDF powder to the volume of the solvent is 1 to 10 g / mL.

[0014] Furthermore, in the step (2), the ratio of the mass of the calcium titanate and graphene oxide composite material prepared by laser liquid phase ablation to the volume of the solvent is 0.02 to 0.3 g / mL.

[0015] Furthermore, the method further comprises step (6), which is specifically as follows: taking the photocatalytic film obtained in step (5), observing whether a regular, periodic array of microstructures is formed on the surface of the photocatalytic film by means of a confocal microscope, determining the light trapping ability of the photocatalytic film surface when the microstructures exist by means of an ultraviolet-visible diffuse reflectance spectrometer, and determining the hydrophilicity of the photocatalytic film surface when the microstructures exist by means of an optical contact angle meter; if no regular, periodic array of microstructures is observed on the surface of the photocatalytic film, the sample is discarded; otherwise, the sample is retained.

[0016] Furthermore, the method further comprises step (7), wherein a methyl orange degradation experiment is performed to study the photocatalytic degradation ability of the photocatalytic film obtained in step (5).

[0017] Furthermore, the step (7) is specifically as follows:

[0018] a. To obtain a standard curve of methyl orange concentration, a methyl orange solution having a concentration of 1 g / L was prepared, and then methyl orange solutions having concentrations of 1 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L and 30 mg / L were obtained by adding deionized water;

[0019] b. Using a UV-visible spectrophotometer to measure the absorbance of methyl orange solutions of different concentrations in step (a), the test wavelength is selected in the range of 200 to 720 nm; taking the absorbance of the methyl orange solution absorption peak at 465 nm and its corresponding concentration to draw a standard curve, taking the x-axis as the concentration and the y-axis as the absorbance, to obtain a linear function relationship between the absorbance and the concentration;

[0020] c. Take the photocatalytic film sample obtained in step (5), the photocatalytic diameter is 50-100nm, add it to a container containing 80-100mL of methyl orange solution, and evaluate the photocatalytic activity of the sample by degrading the methyl orange solution under the irradiation of a 10-15W ultraviolet lamp with a wavelength of 254nm, sampling once every Δt min, 3-5mL at a time, and continue the reaction under light conditions for 10-30min, 2≤Δt≤10; before irradiation, the methyl orange solution mixed with the photocatalytic film is magnetically stirred at a speed of 500-1000rpm for 30-60min under light shielding to achieve adsorption-desorption equilibrium of the photocatalyst;

[0021] d. The sample solution in step (c) is characterized using a UV-visible spectrophotometer, the wavelength of the instrument is selected in the range of 200 to 720 nm, the absorbance of each sample solution at 465 nm is recorded, and the concentration corresponding to the absorbance of each sample solution is obtained according to the standard curve obtained in step (b);

[0022] e. According to the formula Calculation of the kinetic constant K of the photocatalyst x , where x0 is the initial concentration, x Δt is the concentration of the solution at time Δt, K x The larger the value of indicates, the better the catalytic activity;

[0023] f. Take the photocatalytic film samples with different dx and repeat the above steps (a) to (e);

[0024] g. Comparison of the kinetic constant K of the photocatalytic films prepared under different dx x , when it takes the maximum value K max When , it corresponds to the highest catalytic activity, that is, the microstructure prepared under this parameter can make the photocatalytic film have the best activity.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] In the present invention, calcium titanate and graphene oxide composite materials (CTO / rGO composite materials) prepared by laser liquid phase ablation are firstly blended with polyvinylidene fluoride (PVDF) to prepare a photocatalytic film by a blending method, and then the surface of the photocatalytic film is etched by pulsed laser to obtain a pattern microstructure surface with dual functions of hydrophilicity and anti-reflection, thereby improving the reusability of the photocatalyst and enhancing the photocatalytic degradation effect.

[0027] Experiments have shown that the photocatalytic film with a hydrophilic and light-trapping dual-functional microstructure has good photocatalytic activity and recyclability, and maintains its long-term stable photocatalytic degradation ability. On the one hand, the improvement of hydrophilicity is conducive to increasing the contact area between pollutants and the surface of the photocatalytic film, thereby providing more reaction sites, making it easier to remove residual dyes adsorbed on the surface; on the other hand, the improvement of anti-reflection performance will increase the utilization rate of incident light, thereby improving the photocatalytic activity of the photocatalytic film.

[0028] The preparation method is simple and reproducible, which is conducive to large-scale preparation, promotion and industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] Figure 1Schematic diagram of the preparation process of the patterned microstructure on the surface of the CTO / rGO photocatalytic film in the present invention;

[0031] Figure 2 is a concentration-absorbance standard curve of the methyl orange solution in the present invention;

[0032] Figure 3 The photocatalytic activity test results are compared between the CTO / rGO photocatalytic film without microstructure in Comparative Example 1 of the present invention and the CTO / rGO photocatalytic film with hydrophilic and light-trapping dual-functional microstructure with a filling gap dx of 120 μm (CTO / rGO photocatalytic film (120)) prepared in Example 1. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The calcium titanate and graphene oxide composite material (CTO / rGO composite material) prepared by laser liquid phase ablation used in the example is prepared by using a preparation process described in a patent with publication number CN114082412B and patent name "A method for improving the photocatalytic activity of calcium titanate using pulsed laser".

[0035] Example 1

[0036] A method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser comprises the following steps:

[0037] (1) 7 mL of N,N-dimethylformamide (DMF) and 3 mL of acetone were mixed as a solvent, and then 4 g of PVDF powder was added thereto, and then stirred at 800 rpm for 4 h to completely dissolve the PVDF powder;

[0038] (2) adding 0.133 g of calcium titanate and graphene oxide composite material (CTO / rGO composite material) prepared by laser liquid phase ablation to the PVDF solution dissolved in step (1), and continuing stirring for 4 h to obtain a uniformly dispersed mixed solution;

[0039] (3) placing the mixed solution obtained in step (2) in a vacuum desiccator and maintaining the pressure for 4 hours to remove bubbles in the mixed solution;

[0040] (4) drying the mixed solution after treatment in step (3) in a water bath at 70° C. for 6 h to obtain a CTO / rGO photocatalytic film;

[0041] (5) The photocatalytic film prepared in step (4) is subjected to a picosecond laser precision processing system to form a patterned microstructure on its surface, wherein the system is composed of a 1064nm picosecond pulse laser (PINE-1064-30B Huaray), a beam expander, a reflector, an XY electro-vibration scanner and a focusing lens; specifically, the laser irradiation parameters are set: a pulse width of 10ps, a repetition frequency of 100kHz, a focal spot diameter of 20μm, an average pulse energy of the output pulsed Gaussian laser beam of 160μJ, and a scanning speed of 2000mm / s. First, a square with a side length of 2mm is drawn, and a cross groove with a spacing dx of 120μm is filled in the square. After the laser scans the square 100 times, the next square is scanned to obtain the desired patterned microstructure; wherein the laser scans once in the x-axis direction and once in the y-axis direction, which is recorded as one laser scan. The preparation process of the patterned microstructure on the surface of the CTO / rGO photocatalytic film is as follows: Figure 1 As shown;

[0042] (6) taking the photocatalytic film obtained in step (5), observing whether a regular, periodic array of microstructures is formed on the surface of the photocatalytic film by confocal microscopy, determining the light trapping ability of the photocatalytic film when the microstructure exists on the surface of the photocatalytic film by UV-visible diffuse reflectance spectrometer, and determining the hydrophilicity of the photocatalytic film when the microstructure exists on the surface of the photocatalytic film by optical contact angle measurement instrument. If no regular, periodic array of microstructures is observed on the surface of the photocatalytic film, the sample is discarded, otherwise the sample is retained;

[0043] (7) conducting a methyl orange degradation experiment to study the photocatalytic degradation ability of the photocatalytic film obtained in step (5);

[0044] The details are as follows:

[0045] a. To obtain a standard curve of methyl orange concentration, a methyl orange solution having a concentration of 1 g / L was prepared, and then methyl orange solutions having concentrations of 1 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L and 30 mg / L were obtained by adding deionized water;

[0046] b. Using a UV-visible spectrophotometer to measure the absorbance of methyl orange solutions of different concentrations in step (a), the test wavelength is selected in the range of 200 to 720 nm; the absorbance of the methyl orange solution absorption peak at 465 nm and its corresponding concentration are used to draw a standard curve, with the x-axis being the concentration and the y-axis being the absorbance, and the linear function relationship between the absorbance and the concentration y = 0.074x is obtained. The concentration-absorbance standard curve of the methyl orange solution is specifically shown in Figure 2 ;

[0047] c. Take the photocatalytic film sample obtained in step (5), the photocatalytic diameter is 50nm, add it to a container containing 100mL of methyl orange solution, and evaluate the photocatalytic activity of the sample by degrading the methyl orange solution under the irradiation of a 15W ultraviolet lamp with a wavelength of 254nm, Δt is 4min, and the sample is taken once every 4min, 4mL is sampled at a time, and the reaction is continued for 15min under light conditions; before irradiation, the methyl orange solution mixed with the photocatalytic film is magnetically stirred at a speed of 800rpm for 30min under light-shielding conditions to achieve adsorption-desorption equilibrium of the photocatalyst;

[0048] d. The sample solution in step (c) is characterized using a UV-visible spectrophotometer, the wavelength of the instrument is selected in the range of 200 to 720 nm, the absorbance of each sample solution at 465 nm is recorded, and the concentration corresponding to the absorbance of each sample solution is obtained according to the standard curve obtained in step (b);

[0049] e. According to the formula Calculation of the kinetic constant K of the photocatalyst x , where x0 is the initial concentration of methyl orange solution, x Δt is the concentration of methyl orange solution at time Δt, Δt is the interval sampling time, K x The larger the value of indicates, the better the catalytic activity;

[0050] f. Take the photocatalytic film samples with different filling gaps dx and repeat the above steps (a) to (e);

[0051] g. Comparison of the kinetic constant K of the photocatalytic films prepared under different filling gaps dx x , when it takes the maximum value K max When , it corresponds to the highest catalytic activity, that is, the microstructure prepared under this parameter can make the photocatalytic film have the best activity.

[0052] Comparative Example 1

[0053] This comparative example is a comparative test example of Example 1. Compared with Example 1, this comparative example does not form a patterned microstructure on the surface of the CTO / rGO photocatalytic film. The photocatalytic activity of the CTO / rGO photocatalytic film without microstructure prepared in this comparative example is compared with the CTO / rGO photocatalytic film (120) with a hydrophilic and light-trapping dual-functional microstructure with a filling gap dx of 120 μm prepared in Example 1. The photocatalytic activity test results of the two are shown in FIG. Figure 3 .Depend on Figure 3 The test results show that the CTO / rGO photocatalytic film with microstructure has stronger photocatalytic activity.

[0054] In summary, in the present invention, calcium titanate and graphene oxide composite materials (CTO / rGO composite materials) prepared by laser liquid phase ablation are first blended with polyvinylidene fluoride (PVDF) to prepare a photocatalytic film by a blending method, and then a pulsed laser is used to etch the surface of the photocatalytic film to obtain a pattern microstructure surface with dual functions of hydrophilicity and anti-reflection, thereby improving the reusability of the photocatalyst and enhancing the photocatalytic degradation effect. Experiments have shown that the photocatalytic film with a hydrophilic and light-trapping dual-functional microstructure has good photocatalytic activity and recyclability, and maintains its long-term stable photocatalytic degradation ability. On the one hand, the improvement of hydrophilicity is conducive to increasing the contact area between pollutants and the surface of the photocatalytic film, thereby providing more reaction sites, making it easier to remove residual dyes adsorbed on the surface; on the other hand, the improvement of anti-reflection performance will increase the utilization rate of incident light, thereby improving the photocatalytic activity of the photocatalytic film.

[0055] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser, characterized in that: The steps include: (1) Using N,N-dimethylformamide and acetone as solvents, adding PVDF powder thereto, and stirring until PVDF is completely dissolved; (2) adding the calcium titanate and graphene oxide composite material prepared by laser liquid phase ablation to the PVDF solution dissolved in step (1), and continuing to stir to obtain a uniformly dispersed mixed solution; (3) placing the mixed solution obtained in step (2) in a vacuum desiccator and maintaining the pressure for 3 to 5 hours to remove bubbles in the mixed solution; (4) drying the mixed solution after treatment in step (3) in a water bath at 70 to 90° C. for 6 to 8 hours to obtain a photocatalytic film; (5) The photocatalytic film prepared in step (4) is subjected to a picosecond laser precision processing system to form a patterned microstructure on its surface; specifically, the laser irradiation parameters are set: the laser wavelength, scanning speed, laser energy, spot size, spot overlap rate, and scanning area position and size are fixed, firstly a square with a side length of 2 to 10 mm is drawn, and a cross groove with a spacing of dx is filled in the square, and the dx range is 120 to 180 μm. After the laser scans the square 50 to 100 times, the next square is scanned to obtain the desired patterned microstructure; wherein, the laser scans once in the x-axis direction and once in the y-axis direction, which is recorded as one laser scan.

2. The method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser according to claim 1, characterized in that: In the step (1), the volume ratio of N,N-dimethylformamide to acetone in the solvent is 7:3, and the ratio of the mass of PVDF powder to the volume of the solvent is 1 to 10 g / mL.

3. The method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser according to claim 2, characterized in that: In the step (2), the ratio of the mass of the calcium titanate and graphene oxide composite material prepared by laser liquid phase ablation to the volume of the solvent is 0.02 to 0.3 g / mL.

4. The method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser according to claim 1, characterized in that: The method further includes step (6), which is specifically as follows: taking the photocatalytic film obtained in step (5), observing whether a regular, periodic array of microstructures is formed on the surface of the photocatalytic film through a confocal microscope, determining the light trapping ability of the photocatalytic film surface when the microstructure exists through an ultraviolet-visible diffuse reflectance spectrometer, and determining the hydrophilicity of the photocatalytic film surface when the microstructure exists through an optical contact angle meter. If no regular, periodic array of microstructures is observed on the surface of the photocatalytic film, the sample is discarded, otherwise the sample is retained.

5. The method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser according to claim 1, characterized in that: The method further comprises step (7), wherein a methyl orange degradation experiment is performed to study the photocatalytic degradation capability of the photocatalytic film obtained in step (5).

6. The method for preparing a photocatalytic film having a hydrophilic and light-trapping dual-functional microstructure using pulsed laser according to claim 5, characterized in that: The step (7) is specifically as follows: a. To obtain a standard curve of methyl orange concentration, a methyl orange solution having a concentration of 1 g / L was prepared, and then methyl orange solutions having concentrations of 1 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L and 30 mg / L were obtained by adding deionized water; b. Using a UV-visible spectrophotometer to measure the absorbance of methyl orange solutions of different concentrations in step (a), the test wavelength is selected in the range of 200 to 720 nm; taking the absorbance of the methyl orange solution absorption peak at 465 nm and its corresponding concentration to draw a standard curve, taking the x-axis as the concentration and the y-axis as the absorbance, to obtain a linear function relationship between the absorbance and the concentration; c. Take the photocatalytic film sample obtained in step (5), the photocatalytic diameter is 50-100nm, add it to a container containing 80-100mL of methyl orange solution, and evaluate the photocatalytic activity of the sample by degrading the methyl orange solution under the irradiation of a 10-15W ultraviolet lamp with a wavelength of 254nm, sampling once every Δtmin, 3-5mL at a time, and continue the reaction under light conditions for 10-30min, 2≤Δt≤10; before irradiation, the methyl orange solution mixed with the photocatalytic film is magnetically stirred at a speed of 500-1000rpm for 30-60min under light shielding to achieve adsorption-desorption equilibrium of the photocatalyst; d. The sample solution in step (c) is characterized using a UV-visible spectrophotometer, the wavelength of the instrument is selected in the range of 200 to 720 nm, the absorbance of each sample solution at 465 nm is recorded, and the concentration corresponding to the absorbance of each sample solution is obtained according to the standard curve obtained in step (b); e. According to the formula Calculation of the kinetic constant K of the photocatalyst x , where x0 is the initial concentration, x Δt is the concentration of the solution at time Δt, K x The larger the value of indicates, the better the catalytic activity; f. Take the photocatalytic film samples with different dx and repeat the above steps (a) to (e); g. Comparison of the kinetic constant K of the photocatalytic films prepared under different dx x , when it takes the maximum value K max When , it corresponds to the highest catalytic activity, that is, the microstructure prepared under this parameter can make the photocatalytic film have the best activity.